2015
DOI: 10.18632/oncotarget.6740
|View full text |Cite
|
Sign up to set email alerts
|

A subset of myofibroblastic cancer-associated fibroblasts regulate collagen fiber elongation, which is prognostic in multiple cancers

Abstract: Collagen structure has been shown to influence tumor cell invasion, metastasis and clinical outcome in breast cancer. However, it remains unclear how it affects other solid cancers. Here we utilized multi-photon laser scanning microscopy and Second Harmonic Generation to identify alterations to collagen fiber structure within the tumor stroma of head & neck, esophageal and colorectal cancers. Image segmentation algorithms were then applied to quantitatively characterize these morphological changes, showing tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
178
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(188 citation statements)
references
References 53 publications
10
178
0
Order By: Relevance
“…Like hyaluronan, collagen has prognostic value. Worse patient outcome is associated with fibrillar collagen alignment in breast cancer (Conklin et al 2011; Bredfeldt et al 2014), and elongated collagen fibers in patients with head and neck, colorectal, and esophageal cancers (Hanley et al 2016). Experimental studies have shown that the organization and stiffening of the collagen fibers by CAFs facilitates cancer cell invasion (Gaggioli et al 2007; Goetz et al 2011).…”
Section: Tumor Microenvironmentmentioning
confidence: 99%
“…Like hyaluronan, collagen has prognostic value. Worse patient outcome is associated with fibrillar collagen alignment in breast cancer (Conklin et al 2011; Bredfeldt et al 2014), and elongated collagen fibers in patients with head and neck, colorectal, and esophageal cancers (Hanley et al 2016). Experimental studies have shown that the organization and stiffening of the collagen fibers by CAFs facilitates cancer cell invasion (Gaggioli et al 2007; Goetz et al 2011).…”
Section: Tumor Microenvironmentmentioning
confidence: 99%
“…Toward clinical translation, it has already been shown that the detection of TACS in routine histopathological evaluation of breast cancer can serve as an optical biomarker and be predictive of disease recurrence and patient survival. 11 The clinical importance of collagen organization has also been investigated in pancreatic, 12 esophageal, 13 and ovarian cancers.…”
Section: Research-article2016mentioning
confidence: 99%
“…Undoubtedly, SHG has great advantages in terms of imaging depth and higher-order information, but for most of the reported histopathological studies done with standard 5-µm-thick pathology sections, these advantages are not of primary interest. [11][12][13]29 In addition, SHG is not readily accessible in the clinical setting due to high cost, lack of clinical interfaces, and relatively slow acquisition workflows.…”
Section: Research-article2016mentioning
confidence: 99%
“…However, even as high-resolution 3D images of fiber-like tissue structures become more readily accessible, quantitative analysis algorithms for their orientation and organization have largely remained limited to analysis of 2D images [1421], with only a few notable exceptions [2225]. Schriefl et al used polarized microscopy to determine the fiber orientation relying on the birefringence of collagen fibers, by sequentially rotating the sample slide in the azimuthal and the elevation plane to find the two Euler angles to depict an orientation in 3D space.…”
Section: Introductionmentioning
confidence: 99%